Starch-based biofilm reinforced with empty fruit bunch cellulose nanofibre - Salleh, Eraricar (Maney Publishing, 2014)
In general, starch-based biopolymer has low mechanical properties. Hence, various methods have been applied to enhance its properties as well as the incorporation of fibrous nanocellulose. The aim of this study is to enhance the mechanical properties of starch-based polymer by incorporating nanocellulose extracted from oil palm empty fruit bunch. The cellulose nanofibre was obtained by hydrolysing oil palm empty fruit bunch fibre with 64% sulphuric acid at 45°C for 90 minutes. It has diameter between 50 and 90 nm as shown by transmission electron microscopy image. In nanoreinforced starch-based packaging, the amount of nanocellulose loading was varied between 2 and 10% per weight of starch. The tensile strength of 2% cellulose nanofibre incorporated film was increased to 468 MPa, which is 28% higher than the tensile strength exhibited by the native starch-based film, 366 MPa. However, the tensile strength was reduced when cellulose nanofibre incorporation goes beyond 2%. The Young's modulus demonstrates the same pattern as tensile strength, where 2% of cellulose nanofibre gave the optimum results for Young's modulus value. Elongation percentage of nanobiocomposite film also reduced even at low cellulose nanofibre loading, 2%. Regardless of its drawback on elongation percentage, an addition of 2% of cellulose nanofibre is the finest ratio that could improve the mechanical properties of starch-based biopolymer.